Light-transmitting organic quartz stone plate as well as preparation method and application thereof

By designing the matrix slurry and filling it with light-transmitting resin, the existing light-transmitting artificial stone preparation methods are solved, and the naturalness of light-transmitting effect and production efficiency are improved.

CN119659032AActive Publication Date: 2025-03-21CHINA RESOURCES CEMENT TECH R & D (GUANGXI) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510193536.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-21
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

The existing preparation methods for light-transmitting artificial stones are complex, have low production efficiency and high cost. The light-transmitting materials are easily displaced, damaged and interrupted during the pressing process, and the light-transmitting effect is unnatural.

Method used

The matrix slurry is designed by the grading method to form an intertwined pore mesh three-dimensional structure, and fill it with cured translucent resin material. The resin is closely bonded to the substrate to form a dense artificial stone slab.

Benefits of technology

The naturalness of the light transmission effect is achieved, the process is simplified, the production efficiency and product quality are improved, the cost is reduced, and the light transmission aperture and area can be designed arbitrarily.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a light-transmitting organic quartz stone plate as well as a preparation method and application thereof, and relates to the technical field of organic quartz stone plates, the preparation method comprises the following steps: (a) preparing quartz sand aggregate into broken gradation matrix slurry in a broken gradation manner, and distributing and pressing the matrix slurry to obtain a light-transmitting organic quartz stone blank; and (b) distributing the light-transmitting slurry to the light-transmitting area of the quartz stone blank, enabling the light-transmitting slurry to permeate and fill pores of the light-transmitting area, and curing to obtain the light-transmitting organic quartz stone plate. The problems that in the prior art, light-transmitting materials are shifted, damaged and interrupted in the pressing process, and meanwhile light transmission is not natural and rigid are solved, and the technical effects that the procedure is simple, the production efficiency is high, the product quality is stable, the light-transmitting area and the light-transmitting effect are easy to design, and light transmission is more natural are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic quartz stone plates, and in particular to a light-transmitting organic quartz stone plate and a preparation method and application thereof. Background Art

[0002] Organic quartz is mainly made of unsaturated polyester resin as adhesive, adding quartz powder, quartz sand, coarse aggregate and various additives, in a certain proportion and through a certain process. Organic quartz is widely used in various kitchen and bathroom countertops due to its good gloss, hard texture, good decorative effect and high strength.

[0003] With the intensification of market competition and people's yearning for a better life, artificial stones with light-transmitting functions have emerged, which can meet the design of more decorative scenes. At present, the preparation method of light-transmitting artificial stones is mainly to implant optical fibers and resin materials with light-transmitting properties. One method is to pre-implant during the production process of the board, and the other is to open holes and embed after the board is formed. These two methods have relatively complicated processes, low production efficiency, and high costs, and are difficult to apply in large-scale production. In addition, the pre-implantation of light-transmitting materials is prone to quality problems such as breaking and displacement of light-transmitting materials during the board pressing process, affecting light transmission and its decorative effects. At the same time, the light-transmitting materials used in the prior art are mainly in the shape of wires, cables, tubes, and rods, and the light-transmitting apertures are mainly fixed circles and other regular triangles and quadrilaterals, which are in a prescribed pattern, resulting in an unnatural and rigid actual light-transmitting effect.

[0004] The Chinese invention patent application with publication number CN202410080933.X discloses a light-transmitting inorganic artificial stone and a preparation method thereof. In the process of producing inorganic artificial stone by the pressing plate method, holes are punched on a wooden base plate according to the desired pattern, and then PMMA light-transmitting fibers are inserted into the base plate holes. This method is complex to operate, has a large workload, and is time-consuming and labor-intensive to implement. First, the aperture position and aperture size must be accurately controlled. The aperture position deviation will affect the pattern effect. The aperture size deviation will make it impossible to insert the light-transmitting fiber into the aperture or the fit will not be firm and it will easily fall off. If the optical fiber is too thin, the operation will be more difficult and it will be easy to bend. The wooden base plate is placed at the bottom of the mold, and the mixture is evenly spread over the mold. Since the artificial stone slurry is in a semi-dry and wet state and most products contain coarse-grained aggregates, it is difficult to evenly distribute the slurry around the light-transmitting optical fiber, and it is easy to produce material shortage and void problems. The pressing process is high-frequency vibration pressing, and the light-transmitting optical fiber is prone to quality problems such as breaking, bending, and displacement. The wooden base plate mold used to fix the optical fiber is easily damaged and contaminated and cannot be reused.

[0005] The Chinese invention patent application with publication number CN202310474743.1 discloses a luminous and permeable 3D printed concrete material and a construction method thereof. The light-guiding material is selected from wires, cables, tubes or rod-shaped materials made of optical fibers, resins, glass or acrylic materials. The light-guiding connectors are used to connect the light-guiding materials along the arrangement direction, along the strip direction and along the stacking direction to complete a continuous light-guiding skeleton. The construction method of the 3D printed concrete material is used to continuously and integratedly place the light-guiding materials in the printing process along the arrangement direction and along the strip direction. Since the light-guiding material is laid by pouring, it is easy to have the problem of discontinuity of the light-guiding material, blocking the light-guiding performance. At the same time, when the light-guiding materials are continuous and without intervals, there is no cementitious material bonding between the light-guiding materials, and the structural firmness and strength cannot be guaranteed. In the process of pouring the slurry, due to the downward impact force of the slurry under the action of gravity and pumping pressure, it is easy to disperse the light-guiding materials that are closely arranged together to form a cross section, affecting the continuity of the light guide.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] One of the purposes of the present invention is to provide a method for preparing a light-transmitting organic quartz stone plate, which can solve the problems of displacement, breakage and discontinuity in the pressing process of the light-transmitting material used in the prior art, as well as the problem of unnatural and rigid light transmission.

[0008] The second object of the present invention is to provide a light-transmitting organic quartz stone plate with stable quality and more natural light transmission.

[0009] The third object of the present invention is to provide an application of a light-transmitting organic quartz stone plate, which is beneficial to improving the decorative effect of a building and can meet more decorative scene design requirements.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a method for preparing a light-transmitting organic quartz stone plate comprises the following steps: (a) preparing a matrix slurry with a broken gradation by using a broken gradation method, taking the matrix slurry for spreading and pressing to obtain a light-transmitting organic quartz stone embryo; (b) spreading the light-transmitting slurry on the light-transmitting area of ​​the quartz stone body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain the light-transmitting organic quartz stone plate.

[0011] Further, the quartz sand aggregate includes highly reflective quartz sand aggregate; The method for preparing the highly reflective quartz sand aggregate comprises the following steps: Aluminum powder, titanium dioxide, glass beads, adhesive, silicone oil defoamer, 2-(2-hydroxy-5-benzyl)benzotriazole and methyl ethyl ketone peroxide are dispersed and mixed to obtain a reflective coating slurry; The reflective coating slurry and quartz sand are mixed and solidified to obtain the highly reflective quartz sand aggregate.

[0012] Further, the highly reflective quartz sand aggregate includes 26-40 mesh highly reflective quartz sand aggregate and 40-70 mesh highly reflective quartz sand aggregate; The reflectivity of the highly reflective quartz sand aggregate is above 90%.

[0013] Furthermore, the broken-graded matrix slurry is prepared from the following components in parts by weight: 10-50 parts of 26-40 mesh high reflective quartz sand aggregate, 10-50 parts of 40-70 mesh high reflective quartz sand aggregate, 2-5 parts of unsaturated polyester resin, curing agent, and coupling agent; Among them, the amount of curing agent accounts for 0.5%-2.0% of the amount of unsaturated polyester resin; The amount of coupling agent used accounts for 0.5%-2.0% of the amount of unsaturated polyester resin used.

[0014] Furthermore, the porosity of the plate designed in the broken gradation manner is 5%-30%.

[0015] Furthermore, the light-transmitting slurry includes acrylic resin composite light-transmitting slurry; The viscosity of the acrylic resin composite light-transmitting slurry is 80mpa.s-150mpa.s, and the light transmittance after curing is above 90%.

[0016] Furthermore, the light-transmitting slurry penetrates into and fills the pores of the light-transmitting area under the action of negative pressure.

[0017] Furthermore, the curing temperature is 90° C.-110° C., and the curing time is 2 h-3 h.

[0018] In a second aspect, a light-transmitting organic quartz stone plate is prepared by any of the preparation methods described above.

[0019] A third aspect is an application of the above-mentioned light-transmitting organic quartz stone plate in architectural decoration.

[0020] Compared with the prior art, the present invention has at least the following beneficial effects: The preparation method of the light-transmitting organic quartz stone plate provided by the present invention designs the plate formula by means of a discontinuous grading method so that a light-transmitting area is formed on the plate. Specifically, the present invention adopts a matrix slurry with a discontinuous grading design for dispensing so that a porous mesh-like three-dimensional structure that is interconnected and interwoven is formed in the plate, which is water-permeable and light-permeable, and is filled with a resin material (light-transmitting slurry) that is light-permeable after curing. The resin will be tightly bonded to the matrix after curing, thereby forming a dense artificial stone plate. When a light source is irradiated on one side of the plate, the light will be transmitted to the other side of the plate along the internally interconnected and interwoven resin body, and the plate has a natural light-transmitting effect. In short, the preparation method of the present invention is not only simple to operate, low in cost, and high in production efficiency, but also conducive to product promotion and application, and the light-transmitting aperture size and area range can be arbitrarily designed and easily realized, and the light-transmitting effect is more natural, which solves the problems of displacement, breakage and discontinuity in the pressing process of the light-transmitting material used in the prior art, and the problem of unnatural and rigid light transmission.

[0021] The light-transmitting organic quartz stone plate provided by the present invention has stable quality and more natural light transmission.

[0022] The application of the light-transmitting organic quartz stone plate provided by the present invention is conducive to improving the decorative effect of buildings and can meet more decorative scene design requirements. DETAILED DESCRIPTION

[0023] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] According to a first aspect of the present invention, there is provided a method for preparing a light-transmitting organic quartz stone plate, comprising the following steps: (a) preparing a matrix slurry with a broken gradation by using a broken gradation method, and distributing and pressing the matrix slurry to obtain a light-transmitting organic quartz stone embryo; (b) spreading the light-transmitting slurry on the light-transmitting area of ​​the quartz stone body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain a light-transmitting organic quartz stone plate.

[0025] The preparation method of the light-transmitting organic quartz stone plate provided by the present invention designs the plate formula by means of a discontinuous grading method so that a light-transmitting area is formed on the plate. Specifically, the present invention adopts a matrix slurry with a discontinuous grading design for distribution, so that a three-dimensional structure of interlinked pores and a mesh is formed in the plate, which is permeable to water and light, and is filled with a resin material (light-transmitting slurry) that is light-transmitting after curing. After the resin is cured, it will be tightly bonded to the matrix, thereby forming a dense artificial stone plate. When a light source is irradiated on one side of the plate, the light will be transmitted along the internal interlinked resin body to the other side of the plate, and the plate has a natural light-transmitting effect.

[0026] In summary, the preparation method of the present invention is not only simple to operate, low in cost, and has high production efficiency, which is conducive to product promotion and application, but also the light-transmitting aperture size and area range can be arbitrarily designed and easily realized, and the light-transmitting effect is more natural, which solves the problem of displacement, breakage and discontinuity of the light-transmitting materials used in the prior art during the pressing process, and the problem of unnatural and rigid light transmission.

[0027] In a preferred embodiment, the quartz sand aggregate includes but is not limited to highly reflective quartz sand aggregate. For example, the surface of the quartz sand aggregate may be coated with a reflective coating to obtain highly reflective quartz sand aggregate, which is beneficial to improving the light transmittance of the board.

[0028] In the present invention, the preparation method of highly reflective quartz sand aggregate comprises the following steps: Aluminum powder, titanium dioxide, glass beads, adhesive, silicone oil defoamer, 2-(2-hydroxy-5-benzyl)benzotriazole and methyl ethyl ketone peroxide are dispersed and mixed to obtain a reflective coating slurry; The reflective coating slurry and quartz sand are mixed and solidified to obtain highly reflective quartz sand aggregate.

[0029] The surface of the quartz sand aggregate is wrapped with a reflective coating so that the inner wall of the interconnected pores of the board has a reflective effect, thereby effectively improving the light transmittance of the board.

[0030] In a preferred embodiment, the highly reflective quartz sand aggregate includes but is not limited to 26-40 mesh highly reflective quartz sand aggregate and 40-70 mesh highly reflective quartz sand aggregate.

[0031] A typical preparation method of highly reflective quartz sand aggregate comprises the following steps: By weight, 3 parts of aluminum powder, 3 parts of titanium dioxide, 10 parts of glass microspheres, 10 parts of adhesive, 0.05 parts of silicone oil defoamer, 0.05 parts of 2-(2-hydroxy-5-benzyl)benzotriazole and 0.15 parts of methyl ethyl ketone peroxide curing agent were stirred and dispersed for 10 minutes by a 500 r / min high-speed disc disperser to obtain a reflective coating slurry; Measured by weight, 1 part of the obtained reflective coating slurry and 10 parts of quartz sand are added into a 60r / min mixer and stirred for 5 minutes. When pre-cured at 60°C to reach a gel state, they are sprayed into a 180°C high-temperature curing furnace through a 0.04MPa high-pressure air gun for curing treatment to obtain quartz sand aggregate with high reflective performance, that is, high-reflective quartz sand aggregate.

[0032] In the present invention, the reflectivity of the highly reflective quartz sand aggregate can be above 90%.

[0033] In a preferred embodiment, the broken-graded matrix slurry can be prepared from the following components in parts by weight: 10-50 parts of 26-40 mesh high reflective quartz sand aggregate, 10-50 parts of 40-70 mesh high reflective quartz sand aggregate, 2-5 parts of unsaturated polyester resin, curing agent, and coupling agent; Among them, the amount of curing agent (methyl ethyl ketone oxide) can account for 0.5%-2.0% of the amount of unsaturated polyester resin; at the same time, the amount of coupling agent (KH570) can account for 0.5%-2.0% of the amount of unsaturated polyester resin.

[0034] In the present invention, a broken-graded formula design is adopted to obtain a broken-graded matrix slurry, and the porosity of the designed plate can be 5%-30%.

[0035] According to the weight proportion of each component, 26-40 mesh high reflective quartz sand aggregate, 40-70 mesh high reflective quartz sand aggregate, unsaturated polyester resin, curing agent (methyl ethyl ketone oxide) and coupling agent KH570 are put into a mixer and stirred for 3 minutes to 5 minutes to obtain the required matrix slurry.

[0036] In a preferred embodiment, the light-transmitting slurry includes but is not limited to acrylic resin composite light-transmitting slurry, the viscosity of which can be 80mpa.s-150mpa.s, and the transmittance after curing can be above 90%. It not only has high light transmittance, but also can improve permeability, interface adhesion, linear expansion coefficient and aging resistance, etc., and can form an organic whole with the base material to obtain a dense artificial stone slab.

[0037] In a preferred embodiment, the light-transmitting slurry can penetrate into and fill the pores of the light-transmitting area under the action of negative pressure.

[0038] In a preferred embodiment, the curing temperature of the light-transmitting slurry can be 90°C-110°C, and typical but non-limiting temperatures are, for example, 90°C, 95°C, 100°C, 105°C, and 110°C. The curing time can be 2h-3h, and typical but non-limiting times are, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h, and 3h, which is more conducive to obtaining a dense artificial stone slab.

[0039] A typical preparation method of a light-transmitting organic quartz stone plate comprises the following steps: (1) Prepare organic quartz stone plate matrix slurry, recorded as slurry A: By weight, 20-40 parts of quartz sand of 26-40 mesh, 20-40 parts of quartz sand of 40-70 mesh, 20-40 parts of quartz sand of 70-120 mesh, 20-40 parts of quartz powder of 300-500 mesh, 10-20 parts of unsaturated polyester resin, 1-5 parts of pigment, methyl ethyl ketone oxide curing agent (accounting for 0.5%-2.0% of the amount of resin) and coupling agent KH570 (accounting for 0.5%-2.0% of the amount of resin) are put into a mixer and stirred for 3 minutes to 5 minutes to obtain slurry A; (2) Prepare the organic quartz stone plate matrix slurry required for the light-transmitting area, recorded as slurry B: Through the discontinuous grading method, the porosity of the designed plate is 5%-30%; By weight, 10-50 parts of 26-40 mesh high reflective quartz sand aggregate, 10-50 parts of 40-70 mesh high reflective quartz sand aggregate, 2-5 parts of unsaturated polyester resin, methyl ethyl ketone oxide curing agent (accounting for 0.5%-2.0% of the resin amount) and coupling agent KH570 (accounting for 0.5%-2.0% of the resin amount) are put into a mixer and stirred for 3 minutes to 5 minutes to obtain slurry B; Among them, the surface of the highly reflective quartz sand aggregate is coated with a reflective coating with a reflectivity of more than 90%; The method for preparing highly reflective quartz sand aggregate comprises the following steps: By weight, 3 parts of aluminum powder, 3 parts of titanium dioxide, 10 parts of glass microspheres, 10 parts of adhesive, 0.05 parts of silicone oil defoamer, 0.05 parts of 2-(2-hydroxy-5-benzyl)benzotriazole and 0.15 parts of methyl ethyl ketone peroxide curing agent were stirred and dispersed for 10 minutes by a 500 r / min high-speed disc disperser to obtain a reflective coating slurry; 1 part of the obtained reflective coating slurry and 10 parts of quartz sand are added into a 60r / min mixer and stirred for 5 minutes. When the pre-curing reaches a gel state at 60°C, the slurry is sprayed into a 180°C high-temperature curing furnace through a 0.04MPa high-pressure air gun for curing to obtain a quartz sand aggregate with high reflective performance, that is, a high reflective quartz sand aggregate; (3) Select light-transmitting slurry: The selected light-transmitting slurry is acrylic resin composite light-transmitting slurry, the viscosity of which is required to be 80mpa.s-150mpa.s, and the light transmittance after curing is above 90%; (4) Matrix slurry for spreading: If the whole sheet needs to be light-transmissive, only slurry B needs to be spread, and slurry B is evenly spread on the mold with a frame. After the spreading is completed, the next process can be carried out; Alternatively, if only a local area of ​​the board needs to be light-transmissive, the mold is made of PVC board according to the light-transmissive area design plan. First, the non-light-transmissive area is hollowed out, and the hollowed-out PVC board is placed in the mold with a frame. Then, slurry A is spread into the hollowed-out area, and then the PVC board is taken out, and slurry B is filled in the empty area. After the spreading is completed, the next process can be carried out; (5) Pressing the embryo: After the matrix slurry is distributed, it is sent to a press for pressing (press parameters: vibration frequency 250Hz, vacuum degree 0.75bar, pressure 2MPa). After the pressing is completed, a light-transmitting organic quartz stone embryo is obtained; (6) Fabrication with light-transmitting slurry: In the light-transmitting area of ​​the light-transmitting organic quartz stone body, according to the porosity, evenly drip the light-transmitting slurry in the light-transmitting area, then apply it evenly with a brush, and then send it into a press (vacuumable) or a vacuum box, and turn on the vacuum pump for vacuum treatment. The light-transmitting slurry will penetrate into the pores of the light-transmitting area under the action of negative pressure; (7) Baking, curing, maintenance, grinding and polishing: After the light-transmitting slurry is applied, the board is placed at 90℃-110℃ for curing for 2h-3h, the mold is removed, the edges are cut, and the surface is polished to 3000 mesh to obtain an organic quartz stone board with light-transmitting function, which is a light-transmitting organic quartz stone board.

[0040] In short, compared with the prior art, the present invention is simple to operate and does not require tedious processes such as positioning, drilling, and arranging translucent materials, which is conducive to greatly improving production efficiency and achieving stable batch production, and effectively solves the quality problems of the prior art such as displacement, breakage, and discontinuity in the pressing process of translucent materials; at the same time, since the production cost of the method of the present invention is low, which is comparable to the production cost of existing quartz stone slabs, it is conducive to the promotion and application of the product; in addition, the light transmission effect can be designed, the size of the light transmission aperture and the sparseness can be adjusted by the porosity size, and the light transmission area and the light transmission area pattern can be adjusted by the mold The design realizes that the shape of the light-transmitting aperture changes with the design, and the light-transmitting effect is more natural; in particular, the use of specific highly reflective quartz sand aggregate forms a good light reflection effect inside the light-transmitting pores, effectively improving the light-transmitting performance of the board; the selection of specific light-transmitting slurry not only has good permeability and good adhesion to the substrate, but also is basically consistent with the mechanical properties and linear expansion coefficient of the substrate, thus forming an organic whole with the base material; in addition, the color of the light transmitted by the board can be designed, and by adding pigments or dyes of different colors with light-transmitting properties to the light-transmitting slurry, light of colors such as red light, blue light, and fluorescence can be obtained.

[0041] According to a second aspect of the present invention, there is provided a light-transmitting organic quartz stone plate prepared by any of the preparation methods described above.

[0042] The light-transmitting organic quartz stone plate provided by the present invention has stable quality and more natural light transmission.

[0043] According to a third aspect of the present invention, there is provided a use of the above-mentioned light-transmitting organic quartz stone plate in architectural decoration.

[0044] The application of the light-transmitting organic quartz stone plate provided by the present invention is conducive to improving the decorative effect of buildings and can meet more decorative scene design requirements.

[0045] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0046] Example 1 A light-transmitting organic quartz stone plate is prepared by the following preparation method: (a) Organic quartz stone plate matrix slurry, denoted as slurry A, was prepared as follows: By weight, 20 parts of quartz sand of 26-40 mesh, 20 parts of quartz sand of 40-70 mesh, 25 parts of quartz sand of 70-120 mesh, 24 parts of quartz powder of 325 mesh, 10 parts of unsaturated polyester resin, 1 part of pigment, methyl ethyl ketone oxide curing agent (accounting for 1.0% of the amount of resin) and coupling agent KH570 (accounting for 1.0% of the amount of resin) were put into a mixer and stirred for 3 minutes to 5 minutes to obtain slurry A; (b) The organic quartz stone plate substrate slurry required for the light-transmitting area, denoted as slurry B, is prepared by the following preparation method: Through the break grading method, the porosity of the designed plate is 15%; By weight, 50 parts of 26-40 mesh high reflective quartz sand aggregate, 45 parts of 40-70 mesh high reflective quartz sand aggregate, 5 parts of unsaturated polyester resin, methyl ethyl ketone oxide curing agent (accounting for 1.0% of the amount of resin) and coupling agent KH570 (accounting for 1.0% of the amount of resin) were put into a mixer and stirred for 3 minutes to 5 minutes to obtain slurry B; The surface of the highly reflective quartz sand aggregate is coated with a reflective coating with a reflectivity of over 90%; The method for preparing highly reflective quartz sand aggregate comprises the following steps: By weight, 3 parts of aluminum powder, 3 parts of titanium dioxide, 10 parts of glass microspheres, 10 parts of adhesive, 0.05 parts of silicone oil defoamer, 0.05 parts of 2-(2-hydroxy-5-benzyl)benzotriazole and 0.15 parts of methyl ethyl ketone peroxide curing agent were stirred and dispersed for 10 minutes by a 500 r / min high-speed disc disperser to obtain a reflective coating slurry; 1 part of the obtained reflective coating slurry and 10 parts of quartz sand are added into a 60r / min mixer and stirred for 5 minutes. When the pre-curing reaches a gel state at 60°C, the slurry is sprayed into a 180°C high-temperature curing furnace through a 0.04MPa high-pressure air gun for curing to obtain a quartz sand aggregate with high reflective performance, that is, a high reflective quartz sand aggregate; (c) Forming and processing: First, put the hollowed-out PVC board into a mold with a frame, and then spread slurry A into the hollowed-out area. Then take out the PVC board, and fill the empty area with slurry B. Then, send it into a press for pressing (pressing parameters: vibration frequency 250Hz, vacuum degree 0.75bar, pressure 2MPa), press for 2 minutes to obtain a light-transmitting organic quartz stone embryo. A light-transmitting slurry (acrylic resin composite light-transmitting slurry) with a viscosity of 100mpa.s and a light transmittance of 95% after curing is applied to the light-transmitting area of ​​the obtained embryo, and then sent to a press for vacuum treatment. The pressure is maintained at a vacuum degree of 95% for 2 minutes to allow the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area. The obtained plate is placed in a clamping furnace at 100° C. for curing for 2.5 hours, then the mold is removed, the edges are cut, and the surface is polished to 3000 mesh to obtain an organic quartz stone plate with a light-transmitting function, that is, a light-transmitting organic quartz stone plate.

[0047] Example 2 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from the embodiment 1 only in that the entire plate area has light-transmitting properties, that is, in step (c), slurry A is not spread and a hollow mold is not used, but only slurry B is spread and filled; The remaining steps and process parameters are as in Example 1.

[0048] Example 3 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 2 only in that the porosity of the plate is designed to be 30% by the discontinuous gradation of slurry B; The remaining steps and process parameters are as in Example 2.

[0049] Example 4 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from the embodiment 2 only in that 2% of green phosphor is added to the light-transmitting slurry; The remaining steps and process parameters are as in Example 2.

[0050] Example 5 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that in step (b), the highly reflective quartz sand aggregate is replaced with ordinary quartz sand aggregate; The remaining steps and process parameters are as in Example 1.

[0051] Example 6 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (c), the viscosity of the light-transmitting slurry is adjusted to 80 mPa.s; The remaining steps and process parameters are as in Example 1.

[0052] Example 7 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (c), the viscosity of the light-transmitting slurry is adjusted to 150 mpa.s; The remaining steps and process parameters are as in Example 1.

[0053] Example 8 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (c), the viscosity of the light-transmitting slurry is adjusted to 200 mpa.s; The remaining steps and process parameters are as in Example 1.

[0054] Example 9 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (b), the weight portion of the unsaturated polyester resin is 1 part; The remaining steps and process parameters are as in Example 1.

[0055] Example 10 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (b), the weight portion of the unsaturated polyester resin is 2 parts; The remaining steps and process parameters are as in Example 1.

[0056] Embodiment 11 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (b), the weight portion of the unsaturated polyester resin is 3.5 parts; The remaining steps and process parameters are as in Example 1.

[0057] Example 12 This embodiment provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Embodiment 1 only in that, in step (b), the weight portion of the unsaturated polyester resin is 6 parts; The remaining steps and process parameters are as in Example 1.

[0058] Comparative Example 1 This comparative example provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Example 1 only in that, in step (c), the light-transmitting slurry is not applied to the light-transmitting area of ​​the obtained embryo body; The remaining steps and process parameters are as in Example 1.

[0059] Compared with Example 1, the defect of the quartz stone plate obtained in this comparative example is that there are many holes on the plate surface in the light-transmitting area, and the appearance quality of the plate does not meet the product standards of quartz stone plates.

[0060] Comparative Example 2 This comparative example provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Example 1 only in that, in step (c), the light-transmitting slurry is replaced with an unsaturated polyester resin composite light-transmitting slurry; The remaining steps and process parameters are as in Example 1.

[0061] Compared with Example 1, the defect of the quartz stone plate obtained in this comparative example is that the mechanical properties and light transmittance of the plate in the light-transmitting area are reduced to a certain extent.

[0062] Comparative Example 3 This comparative example provides a light-transmitting organic quartz stone plate and a preparation method thereof, which is different from Example 1 only in that, in step (c), the plate is not cured; The remaining steps and process parameters are as in Example 1.

[0063] Compared with Example 1, the defect of the quartz stone plate obtained in this comparative example is that the plate cannot solidify by itself and has no strength.

[0064] Test example The light-transmitting organic quartz stone plates obtained in various embodiments and comparative examples were tested, and the results are shown in Table 1.

[0065] Transmittance test method: polish the translucent area of ​​the translucent artificial stone to a thickness of 20mm, polish both sides to 3000 mesh, cut into 100mm*100mm*20mm samples, use a transmittance meter to test the transmittance of the samples, and measure the transmittance data of the samples.

[0066] Bending strength and appearance quality test method: Test according to the method in standard GB / T 41919-2022 "Artificial Stone Building Board".

[0067] Light transmission color test method: grind the light-transmitting area plate of the light-transmitting artificial stone to a thickness of 20mm, grind both sides to 3000 mesh, cut into 300mm*300mm*20mm samples, put the samples into the light transmission hole reserved in the closed light-shielding room, and observe the color of the light projected on the other side when the samples are exposed to sunlight.

[0068] Table 1

[0069] It can be seen that the present invention not only solves the problems of displacement, breakage and discontinuity of the light-transmitting materials used in the prior art during the pressing process, as well as the problem of unnatural and rigid light transmission, but also achieves the technical effects of simple process, high production efficiency, stable product quality, easy design of light-transmitting areas and light-transmitting effects, and more natural light transmission.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a light-transmitting organic quartz stone plate, characterized in that: The following steps are involved: (a) preparing a matrix slurry with a broken gradation by using a broken gradation method, taking the matrix slurry for spreading and pressing to obtain a light-transmitting organic quartz stone embryo; The broken-graded matrix slurry is prepared from the following components in parts by weight: 10-50 parts of 26-40 mesh high reflective quartz sand aggregate, 10-50 parts of 40-70 mesh high reflective quartz sand aggregate, 2-5 parts of unsaturated polyester resin, curing agent, and coupling agent; (b) spreading the light-transmitting slurry on the light-transmitting area of ​​the quartz stone body, allowing the light-transmitting slurry to penetrate and fill the pores in the light-transmitting area, and solidifying to obtain the light-transmitting organic quartz stone plate; The light-transmitting slurry includes acrylic resin composite light-transmitting slurry; The viscosity of the acrylic resin composite light-transmitting slurry is 80mpa.s-150mpa.s, and the light transmittance after curing is above 90%.

2. The preparation method according to claim 1, characterized in that: The method for preparing the highly reflective quartz sand aggregate comprises the following steps: Aluminum powder, titanium dioxide, glass beads, adhesive, silicone oil defoamer, 2-(2-hydroxy-5-benzyl)benzotriazole and methyl ethyl ketone peroxide are dispersed and mixed to obtain a reflective coating slurry; The reflective coating slurry and quartz sand are mixed and solidified to obtain the highly reflective quartz sand aggregate.

3. The preparation method according to claim 2, characterized in that: The reflectivity of the highly reflective quartz sand aggregate is above 90%.

4. The preparation method according to claim 1, characterized in that: The amount of the curing agent is 0.5%-2.0% of the amount of the unsaturated polyester resin; The amount of the coupling agent used accounts for 0.5%-2.0% of the amount of the unsaturated polyester resin used.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The porosity of the plate designed in the above-mentioned break-gradation mode is 5%-30%.

6. The preparation method according to claim 1, characterized in that: The light-transmitting slurry penetrates and fills the pores in the light-transmitting area under the action of negative pressure.

7. The preparation method according to claim 1, characterized in that: The curing temperature is 90° C.-110° C., and the curing time is 2 h-3 h.

8. A light-transmitting organic quartz stone plate prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the light-transmitting organic quartz stone plate according to claim 8 in architectural decoration.

Citation Information

Patent Citations

  • Light-emitting water-permeable 3D printing concrete material and construction method thereof

    CN116621544A

  • Light-transmitting inorganic artificial stone and preparation method thereof

    CN118005344A

  • Method for preparing high-gloss high-permeability artificial colored quartz plate

    CN104261727A

  • Artificial jade board and manufacturing process thereof

    CN106495560A

  • Semi-transparent ceramic sheet employing light-absorbing decoration of ink and preparation method of semi-transparent ceramic sheet

    CN107010976A